Single-Shot, Turbo Spin-Echo, Diffusion-Weighted Imaging versus Spin-Echo-Planar, Diffusion-Weighted Imaging in the Detection of Acquired Middle Ear Cholesteatoma - De Foer, B. (AJNR Am J Neuroradiol, 2006)
SUMMARY: Diagnosis of acquired middle ear cholesteatoma on MR imaging is mostly done on late postgadolinium T1-weighted MR images and/or echo-planar (EPI) diffusion-weighted (DWI) MR images. We describe the appearance of a case of a complicated attical middle ear cholesteatoma on single-shot (SS) turbo spin-echo (TSE) DWI compared with EPI-DWI. This case suggests a higher reliability of SS TSE-DWI in the diagnosis of acquired middle ear cholesteatoma.